The Implementation of the Semester Credit System (SKS) in Arabic Language Learning at State Islamic Junior High School 1 Bukittinggi: A Qualitative Descriptive Study - Nur Fadhilah Arifin; Yelfi Dewi; Eka Rizal (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This study investigates the implementation of the Semester Credit System (SKS) in Arabic language learning at MTsN 1 Bukittinggi. It aims to describe the preparation, implementation, and supporting and inhibiting factors of SKS-based Arabic instruction. This research employed a descriptive qualitative approach. Data were collected through classroom observation, semi-structured interviews with the vice principal for teacher, and documentation of learning materials, including UKBM. The findings show that SKS implementation requires teacher readiness, student preparation, parental involvement, and institutional support. In classroom practice, Arabic learning is conducted through introductory, core, and closing activities, with students working independently through UKBM according to their learning pace. Supporting factors include collective commitment, institutional legitimacy, curriculum flexibility, and learning facilities. Inhibiting factors include limited public understanding, the complexity of differentiated instruction, and unequal teacher. Practically, these findings imply that Arabic teachers must transition into adaptive instructional designers who optimize UKBM to foster independent problem solving across the four languange skill and implement dynamic scaffolding to bridge diverse student learning paces.